Adipocyte precursor cells from first degree relatives of type 2 diabetic patients feature changes in hsa‐mir‐23a‐5p, ‐193a‐5p, and ‐193b‐5p and insulin‐like growth factor 2 expression. Issue 4 (12th March 2021) - Mirra, Paola; Desiderio, Antonella; Spinelli, Rosa; Nigro, Cecilia; Longo, Michele; Parrillo, Luca; D'Esposito, Vittoria; Carissimo, Annamaria; Hedjazifar, Shahram; Smith, Ulf; Formisano, Pietro; Miele, Claudia; et al.
Abstract: First‐degree relatives (FDRs) of type 2 diabetics (T2D) feature dysfunction of subcutaneous adipose tissue (SAT) long before T2D onset. miRNAs have a role in adipocyte precursor cells (APC) differentiation and in adipocyte identity. Thus, impaired miRNA expression may contribute to SAT dysfunction in FDRs. In the present work, we have explored changes in miRNA expression associated with T2D family history which may affect gene expression in SAT APCs from FDRs. Small RNA‐seq was performed in APCs from healthy FDRs and matched controls and omics data were validated by qPCR. Integrative analyses of APC miRNome and transcriptome from FDRs revealed down‐regulated hsa‐miR‐23a‐5p, ‐193a‐5p and ‐193b‐5p accompanied by up‐regulated Insulin‐like Growth Factor 2 ( IGF2 ) gene which proved to be their direct target. The expression changes in these marks were associated with SAT adipocyte hypertrophy in FDRs. APCs from FDRs further demonstrated reduced capability to differentiate into adipocytes. Treatment with IGF2 protein decreased APC adipogenesis, while over‐expression of hsa‐miR‐23a‐5p, ‐193a‐5p and ‐193b‐5p enhanced adipogenesis by IGF2 targeting. Indeed, IGF2 increased the Wnt Family Member 10B gene expression in APCs. Down‐regulation of the three miRNAs and IGF2 up‐regulation was also observed in Peripheral Blood Leukocytes (PBLs) from FDRs. In conclusion, APCs from FDRs feature a specific miRNA/gene profile, which associates with SAT adipocyte hypertrophy and appears to contribute to impaired adipogenesis. PBL detection of this profile may help in identifying adipocyte hypertrophy in individuals at high risk of T2D.